Role of Antihelminthic Drug and Health Education in Reducing Helminthic Infestation Rate Among the Rural Children - Hossain Ansari, Md Mostaque (TAJ: Journal of Teachers Association, 2011)
Intestinal Helminthiasis is one of the major causes of childhood malnutrition in Bangladeshi rural children. This case control study was undertaken to observe the comparative role of antihelminthic drug and Health Education in reducing the Incidence rate of helminthic infestation in rural primary school children. Three Primary schools were selected in different union of Dhamoirhat thana in Naogaon district. Saline preparation of stool of all students in three schools were done in first week of May, August and November 1997 blindly. Tablet Mebendazole was given only to the students with positive finding of stool for helminthic ova in first school (D R School). After each examinations, health education was conducted in the second school (H E School) one hour weekly since the beginning of the study irrespective of findings and no intervention was done in the third school (C O School) taken as control group. Quarter yearly (in three months) incidence rate in D R School were 8.1% and 8.3%, in H E School were 14.5% and 23.5% and in C O School were 9.1% and 18.3% (in population at risk) in the study. Analysis shows the significant role of anti helminthic drug in reducing the incidence rate besides the prevalence than health education (P value 0.0007). Recommendation was made to continue the mass deworming program as it reduces the reservoirs despite the environmental factors sufficiently enough for transmission of the disease in Bangladesh perspective. DOI: http://dx.doi.org/10.3329/taj.v14i2.8389 TAJ 2001; 14(2): 70-73